Transurethral lidocaine (100 mg) bladder irrigation (TULI100) reduces the incidence of catheter related bladder discomfort in transurethral resection of bladder tumors: A randomized, double blind, controlled trial. (14th November 2022) - Singh, Ajay; Kayina, Choro Athiphro; Naik, Naveen; Ganesh, Venkata; Kumar, Sumit; Pandey, Vijayant Kumar; Bora, Girdhar S.; Saini, Kulbhushan; Soni, Shiv Lal; Kaloria, Narender; Samra, Tanvir; Saini, Vikas
Abstract : Background: Transurethral resection of bladder tumors (TURBT) surgeries requires post‐resection catheterization for continuous irrigation of the bladder. This indwelling catheter is associated with distressing catheter‐related bladder discomfort (CRBD) and increases postoperative pain and agitation. Objectives: To prove the hypothesis that transurethral 100 mg lidocaine irrigation at the end of TURBT can reduce the frequency of moderate‐to‐severe postoperative CRBD. Methods: 116 patients scheduled for TURBT were screened, 94 were recruited and completed the study. American Society of Anesthesiologists Physical Status I–II adult patients, 20–75 years of age undergoing elective TURBT surgery under general anesthesia were included. Transurethral normal saline with 0.01% lidocaine (100 mg in 1 L NS) was used for irrigation 30 min before the completion of surgery in group L, while only normal saline was used for transurethral irrigation in group N. The main outcomes were frequency of CRBD, pain and patient satisfaction at 0, 1, 2, and 6 h postoperatively. Results: A total of 94 patients were analyzed in the study. The incidence of moderate–severe CRBD was significantly lower in group L as compared to group C at 0, 1, and 2 h (65.9% vs. 31.9%, p  = 0.01; 31.9% vs. 10.6%, p  = 0.012; 21.3% vs. 2.1%, p  = 0.004, respectively). At the 6‐h mark, the incidence of CRBD was lower in group L, although this did not achieve statistical significance (6.38% vs. 2.1%; p  = 0.613). Conclusion: Irrigation with 0.01% lidocaine (100 mg) towards the end of TURBT reduces the incidence of moderate–severe CRBD by 52% and increases patient satisfaction.